Load Forecasting for Economic Power Generation and Distribution in Smart Grid Environment - Sastry, Anand Bharadwaj BV; N, Satish Kumar; CR, Manjunath; C, Prasanna Kumar (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Accurate Load Forecasting of electricity demand is vital for any power utility to reduce losses and to increase efficiency. This is vital for implementation of Smart Grid across the country as Load Forecasting helps to provide reliable and quality power supply to the consumer. In this paper we shall compare some of the existing methods that are used for load forecasting and compare the performance of each of those methods using the RMS E value to measure the performance. The method with the least RMS E value performs better having reliable level of accuracy. We have considered the holidays and temperature of the area information also in our work as it greatly influences the load consumption pattern among the consumers.